2019
DOI: 10.1021/acs.jpclett.9b00591
|View full text |Cite
|
Sign up to set email alerts
|

Exciton Binding Energy of Two-Dimensional Highly Luminescent Colloidal Nanostructures Determined from Combined Optical and Photoacoustic Spectroscopies

Abstract: Reduced dimensionality of structures such as 0D quantum dots, 1D nanorods, and 2D nanoplatelets is predicted to favor the creation of tightly bound excitons stable at room temperature, making experimental determination of the exciton binding energy (R x ) crucial for evaluating the performance of semiconductor nanoparticles. We propose a fully optical approach for R x determination based on a complementary combination of photoacoustic and transmission spectra, using 5.5, 4.5, and 3.5 ML CdSe nanoplatelets as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
50
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 48 publications
10
50
2
Order By: Relevance
“…This model represents a simple and accessible tool to probe excitonic and continuum transitions from absorption measurements, complementing sophisticated techniques such as magneto-optical spectroscopy or opto-acoustic methods which were previously used. 20,44 We also explore the effect of dielectric screening on NPL excitons using a simple semiempirical electrostatic model, which produced calculated 's that are in excellent agreement to measured binding energies for 3-5 ML CdSe NPLs. The model confirmed that unlike their bulk and 0D counterparts, nanoplatelet excitonic electrostatic field lines extend beyond the semiconductor itself and are modulated by the external environment.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This model represents a simple and accessible tool to probe excitonic and continuum transitions from absorption measurements, complementing sophisticated techniques such as magneto-optical spectroscopy or opto-acoustic methods which were previously used. 20,44 We also explore the effect of dielectric screening on NPL excitons using a simple semiempirical electrostatic model, which produced calculated 's that are in excellent agreement to measured binding energies for 3-5 ML CdSe NPLs. The model confirmed that unlike their bulk and 0D counterparts, nanoplatelet excitonic electrostatic field lines extend beyond the semiconductor itself and are modulated by the external environment.…”
Section: Discussionmentioning
confidence: 84%
“…We experimentally confirm the effect of dielectric confinement by modifying NPL external environment and showing a noticeable shift in exciton binding energy, consistent with similar measurements in 2D TMDCs and perovskites. 28,42,44 Uncovering the exciton binding energies of NPLs and understanding how external dielectric screening modulates these resonances further establishes the distinct properties of nanoplatelets that distinguish them from their quantum dot counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…High spatial anisotropy translates into a set of hallmark properties of NPLs, ie, characteristically narrow photoluminescence (PL) spectra, high quantum yields (QYs) of luminescence, phenomenally short emission lifetimes, 3 and as we have recently showed, it can also effect in high exciton binding energies, as shown for CdSe NPLs. 4 The latter property, assisted by low Auger recombination rates may lead to possible applications in lasing 5 and in novel photonic devices. 6 Additionally, quantum yields largely exceed those of 0D quantum dots (QDs), being as high as 45%.…”
Section: Introductionmentioning
confidence: 99%
“…From this two-photon scheme, an exciton binding energy, the minimum energy necessary to remove both the electron and hole components from their locations [44], of 128 ± 15 meV was determined and the ZA, TA, LA, TO, and LO phonon modes were identified. This large exciton binding energy is larger than diamond or AlN, suggesting strong luminescence from exciton recombination [45] and thermal stability. Exciton binding energy and oscillator strength have a direct relationship, where high levels of one indicate high levels of the other [46], this interaction leads to exciton-photon coupling [45].…”
Section: Electronic and Dielectric Propertiesmentioning
confidence: 93%
“…This large exciton binding energy is larger than diamond or AlN, suggesting strong luminescence from exciton recombination [45] and thermal stability. Exciton binding energy and oscillator strength have a direct relationship, where high levels of one indicate high levels of the other [46], this interaction leads to exciton-photon coupling [45]. where 0 and are the vacuum permittivity and vacuum permeability, E and H are the electric and magnetic fields, and and are the relative permittivity and relative permeability, respectively.…”
Section: Electronic and Dielectric Propertiesmentioning
confidence: 93%